Outcomes of heart transplantation in patients with human immunodeficiency virus. Issue 5 (25th January 2019) - Madan, Shivank; Patel, Snehal R.; Saeed, Omar; Sims, Daniel B.; Shin, Jooyoung Julia; Goldstein, Daniel J.; Jorde, Ulrich P.
Abstract : Human immunodeficiency virus–positive (HIV+) patients are not routinely offered heart transplantation (HT) due to lack of adequate outcomes data. Between January 2004 and March 2017, we identified 41 adult (≥18 years) HT recipients with known HIV+ serostatus at the time of transplant in UNOS and evaluated post‐HT outcomes. Overall, Kaplan‐Meier (KM) estimates of survival at 1 and 5 years were 85.9% and 77.3%, respectively, with no significant difference in bridge‐to‐transplant ventricular‐assist device (BTT‐VAD, n = 22) and no‐BTT‐VAD (n = 19). KM estimates of cardiac allograft vasculopathy (CAV) and malignancy at 5 years were 32% and 19%, respectively. Using propensity scores, 41 HIV+ HT recipients were matched to 41 HIV‐ HT recipients for idiopathic dilated‐cardiomyopathy; and there was no significant difference in post‐HT survival up to 5 years. Furthermore, only 24 centers in the United States had performed HIV+ HT during the study period, indicating that >80% of HT centers in the United States had not performed any HIV+ HT. In a cohort representative of the current status of HIV+ HTs in the United States, we found that the posttransplant survival was excellent and rates of CAV and malignancy were comparable to the overall HT population. These results should encourage greater number of centers to offer HT to suitable HIV+ candidates and help reduce unequal access to HT for HIV+ patients. Abstract : In a large cohort of HIV+ heart transplants, the authors find that HIV+ patients have excellent posttransplant outcomes similar to HIV‐ patients, results which should help reduce unequal access to heart transplantation for HIV+ patients.